QUANTUM LEARNING DAN FITRAH MANUSIA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Fitriyani, Feny Nida (Institut Daarul Qur'an Jakarta, Indonesia, 2021)
This study aims to analyze the quantum learning theory that can jump-start a person's potential as a manifestation of God's human nature. This research method uses literature or literature research. This research is qualitative in nature which prioritizes the excavation, discovery, reading, explanation and delivery of the express and implied meanings or symbols of the data collected. Descriptive, philosophical and theoretical data analysis or processing. The results of this study are: 1) The concept of quantum learning, namely TANDUR, is an abbreviation of several principles, namely: a. Grow, b. Natural, c. Name, d. Demonstrate, e. Repeat, and f. Celebrate. and 2) The human instinct wants comfort and happiness in various situations, in this case quantum learning can harmonize the three elements (id, ego, super ego) that humans have in the learning process.